Isolation of lignans glycosides from Alibertia sessilis (Vell.) K. Schum. (Rubiaceae) by preparative high-performance liquid chromatography - da Silva, Viviane Cândida; Silva, Geraldo Humberto; Bolzani, Vanderlan da Silva; Lopes, Márcia Nasser (Eclética Química, 2006)
Enantiomeric aglycone lignans contained in a mixture were separated from a fraction of the extract of the stems of Alibertia sessilis (Vell.) K. Schum. (Rubiaceae) by preparative high-performance liquid chromatography. An efficient and fast separation can be achieved with methanol-water (30:70, v/v). Their structures were identified as (+)-lyoniresinol 3alpha-O-beta-glucopyranoside and (-)-lyoniresinol 3alpha-O-beta-glucopyranoside, being reported for the first time in Rubiaceae.